A two-fold interfacial electric-field strategy: boosting the performance of electron transport layer-free perovskite solar cells with low-cost and versatile inorganic acid treatment. Issue 37 (27th August 2021) - Duan, Hui; Li, Xin; Gou, Yue; Wang, Haoyan; Fan, Lin; Chen, Yanli; Yang, Jinghai; Yang, Lili; Wang, Fengyou
Abstract : A two-fold interfacial electric-field strategy was developed for ETL-free PSCs via low-cost and versatile inorganic acid treatment, enabling a high photovoltaic performance (>19.3%). Abstract : Perovskite solar cells without electron transport layers (ETL-free PSCs) have the advantages of low manufacturing costs and simple processes and have attracted wide attention. However, compared to the performance of devices with ETLs, that reported for ETL-free PSCs remains unsatisfactory. Owing to the lack of an ETL, the indium tin oxide (ITO)/perovskite interface energy level does not match and the interface charge recombination is particularly serious, resulting in poor device performance. This issue was solved in this study by implementing electric field engineering on ETL-free PSCs via a simple, low-cost, and non-toxic inorganic acid treatment (IAT). This IAT can modulate the interfacial electric field by adjusting the work function of ITO and optimizing the energy-level structure at the ITO/perovskite interface. Simultaneously, a dipole layer is formed at the ITO/perovskite interface, which enhances the interfacial electric field. Moreover, the inorganic acid radical can serve as a template to modulate the growth of the perovskite layer. Therefore, these three benefits suppress the electron–hole recombination and favor the interfacial charge transfer, increasing the power conversion efficiency of ETL-free PSCs from 14.05% to 19.32%. This approach is anticipated to serve as a general method for ETL-free architecture design in perovskite photovoltaic applications.